The Economic Growth Debate - Geography versus Institutions: Is There Anything Really New? - Andreas Lorenz; Hans-Rimbert Hemmer; Sebastian Ahlfeld (Justus-Liebig-Universität Gießen, Professur für Volkswirtschaftslehre und Entwicklungsländerforschung, 2005)
International analysis of economic growth has confirmed the theoretical assumption that international variations in per capita income can to a large extent be explained by differences in the accumulation of capital and human capital and by differing rates of technological progress. However, these results do not provide an answer to the question as to what causes trans-national variations in accumulation rates and technological progress. In searching for the ultimate drivers of economic growth, three competing lines of explanation have emerged: ? The geography-hypothesis which assumes that economic growth is ultimately determined by geographical characteristics ? The institutions-hypothesis which views the quality of institutions as a fundamental driver of growth ? The policy-hypothesis which emphasises the importance of economic policy This paper provides an overview over these three hypotheses and revisits the debate over their empirical relevance. Comparing the three approaches leads to the conclusion that none of them is really new and that many of their findings have already been incorporated into the strategies for international development assistance. Furthermore, the three hypotheses are not as exclusive as the debate on geography versus institutions would suggest but are indeed interconnected and complementary.
Keywords: O40; O10; 330; Entwicklung; Wirtschaftswachstum; Wirtschaftsgeographie; Institutionalismus; Wirtschaftspolitik; Entwicklungsländer